2017
DOI: 10.1002/dta.2292
|View full text |Cite
|
Sign up to set email alerts
|

MDA, MDMA, and other “mescaline‐like” substances in the US military's search for a truth drug (1940s to 1960s)

Abstract: This article describes the context in which 3,4-methylenedioxyamphetamine (MDA), 3,4-methylenedioxymethamphetamine (MDMA) and other mescaline-like compounds were explored as hallucinogens for military and intelligence purposes from the 1940s to the 1960s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
9
0
3
Order By: Relevance
“…These risks are further amplified by the fact that incarcerated populations are largely Hispanic and Black, as minority populations have historically been subject to mistreatment and abuse within medical research (Brandt, 1978). Coercive experimentation on the incarcerated can have can have deleterious effects (Brecht et al, 2005), and there is a history of state agencies inappropriately and coercively testing psychedelic compounds to manipulate behavior (Passie and Benzenhöfer, 2018; Savage, 1952). Therefore, rigorous ethical frameworks are essential when seeking to further explore the link between psychedelics and crime.…”
Section: Discussionmentioning
confidence: 99%
“…These risks are further amplified by the fact that incarcerated populations are largely Hispanic and Black, as minority populations have historically been subject to mistreatment and abuse within medical research (Brandt, 1978). Coercive experimentation on the incarcerated can have can have deleterious effects (Brecht et al, 2005), and there is a history of state agencies inappropriately and coercively testing psychedelic compounds to manipulate behavior (Passie and Benzenhöfer, 2018; Savage, 1952). Therefore, rigorous ethical frameworks are essential when seeking to further explore the link between psychedelics and crime.…”
Section: Discussionmentioning
confidence: 99%
“…In 1952, a patient named Harold Blauer was administered several compounds over the course of a month before succumbing to a fatal dose of MDA (450 mg). 258 Realizing that safety data on these compounds were woefully lacking, the military contracted a group at the University of Michigan to conduct pharmacokinetic and safety studies in mice, rats, guinea pigs, dogs, and monkeys. 259 After declassification, these data were published in 1973 and revealed that the methylenedioxy compounds were more toxic than their methoxy counterparts.…”
Section: History and Importance In Neurosciencementioning
confidence: 99%
“…Research on MDMA appeared to stagnate until the 1950s. At that time the US military began using mescaline-like compounds, including MDMA, as part of pharmacologically assisted interrogation programs . In essence, they were trying to identify so-called “truth drugs”compounds capable of lowering inhibitions making people more likely to reveal secret information.…”
Section: History and Importance In Neurosciencementioning
confidence: 99%
“…MDMA is a synthetic drug which belongs to the substance class of amphetamines and is structurally similar to the psychedelic hallucinogen mescaline (18). Dual use of MDMA and cannabis is especially prevalent in 15-16 year old adolescents, with 8-13% of whom report having used both substances within the past month (19).…”
Section: Introductionmentioning
confidence: 99%